PT INKA's Export Marketing Strategy Towards Competitive Advantage - Noviati, Putri; Nuraina, Elva; Sulistyowati, Nur Wahyuning (SENTRALISASI, 2022)
This study aims to analyze PT INKA's export marketing strategy towards competitive advantage until 2018. Researchers use primary and secondary data sources with interview and documentation data collection techniques. The results of the study revealed that PT. INKA has: (1) Strength, very competitive pricing power and strong human resources, especially the marketing team, in addition to the influence of marketing assistance from the ambassador (RI for overseas); (2) Weaknesses in the export marketing strategy lie in production, one of which is engines and wheels which are still imported by China, which does not yet have the International Railway Industry Standard Certification (IRIS); (3) Opportunities, can make efforts to further strengthen the penetration of Indonesian companies in the African region; (4) Threats, to providers of facilities and infrastructure needs that must be obtained from imports from other countries, besides that competitors are afraid to dare to reduce interest costs or extend the tenor for the purchase of goods. The high taxes that must be issued for the delivery of goods are the biggest threat, this is confirmed by the informants.